Efficacy of Antiviral Agents against Omicron Subvariants BQ.1.1 and XBB - Imai, Masaki; Ito, Mutsumi; Kiso, Maki; Yamayoshi, Seiya; Uraki, Ryuta; Fukushi, Shuetsu; Watanabe, Shinji; Suzuki, Tadaki; Maeda, Ken; Sakai-Tagawa, Yuko; Iwatsuki-Horimoto, Kiyoko; Halfmann, Peter J.; et al. (The New England journal of medicine, 2023)
Neither bebtelovimab nor any mAb combinations tested neutralized the SARS-CoV-2 omicron subvariants BQ.1.1 and XBB, but remdesivir, molnupiravir, and nirmatrelvir were efficacious against both in vitro.